PEMANFAATAN PEKARANGAN RUMAH MENGGUNAKAN SISTEM KRPL UNTUK MENUNJANG KETAHANAN PANGAN RUMAH TANGGA DESA PRINGGAJURANG UTARA - Mujaddid Muskhul Wahid; Suhaemi, Suhaemi; Lestari, Novia Suci; Putra, Lalu Panji Wira; Hartika, Hartika; Novita, Mia; Mahdani, Alif Rizaldi; Sulistiawati, Bq. Lala; Al Azizi, M. Alfan Habib; Wati, Siti Alfira (Jurnal Wicara, 2025)
The yard is an open area located around a house. If this land is well maintained, it will provide an attractive, comfortable, healthy and pleasant environment so that people feel at home. The purpose of this KKN is to increase knowledge, skills, awareness and motivate the community, especially in North Pringgajurang Village in utilizing empty land or yards as a source of food security and family income and implementing several simple planting and maintenance techniques that can be easily implemented by the community. The method used in this activity is counseling and continued with discussions with villagers as a process to transfer knowledge and skills. The output achievements produced based on the counseling activities include: there is a maximum change in the function of the yard, increasing the knowledge and skills of community groups in implementing vegetable and medicinal plant cultivation techniques, the community already understands the importance of food diversification and the health of the food consumed, and understands the management of family income by selling the harvest of the vegetables. This makes the environment around the activity cleaner and greener, and community groups can meet the needs of vegetables and medicinal plants around their homes.